Commodity price stabilization: The need for a policy mix that breaks the vicious cycle of commodity dependence and price volatility - Bernhard Tröster (Austrian Foundation for Development Research (ÖFSE), 2018)
The concept of the 'resource curse' has typically been used to explain the adverse effects of resource abundance on economic growth and development. More recently, however, the validity of this approach has been challenged. Not the abundance of natural resources per se, but the ability to cope with the volatility of commodity prices is now seen as one of the major factors for the development of commodity-dependent low-income countries (CDLICs). The reduction of economic uncertainty caused by unstable commodity prices is therefore a central policy objective. Policy interventions at both, the global regional and national level targeting commodity price stability are necessary for resource-rich countries in order to implement commodity-based development strategies, which can ultimately lead to structural change.
Keywords: 330